The Benefits of Automated Machine Learning in Hospitality - Castelli, Mauro (2022)
Castelli, M., Pinto, D. C., Shuqair, S., Montali, D., & Vanneschi, L. (2022). The Benefits of Automated Machine Learning in Hospitality: A Step-By-Step Guide and AutoML Tool. Emerging Science Journal, 6(6), 1237-1254. https://doi.org/10.28991ESJ-2022-06-06-02. Funding:This study was supported by grant DSAIPA/DS/0113/2019 from FCT (Fundação para a Ciência e a Tecnologia), Portugal. This work was also supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project - UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.